(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This research explores the opinions of the students in science and class in the area of socio-science and their expertise in the application of socio-scientific questions in the teaching of science and technology. The thesis followed a qualitative approach to analysis, and the participant determination criteria survey methodology was used. The data from this analysis were obtained through a questionnaire comprising five questions that were open-ended. In the academic years 2009-2010, data for the study were obtained at the Summer School and evaluated through descriptive analyses. It was discovered that instructor applicants conceptualize socio-scientific problems in multiple forms. When the meanings are analyzed in general, it is found that the characteristics of social and science questions are recent phenomena that have a scientific foundation that have an impact on human and societal existence. Candidates for teachers claim that they are incompetent to use cognitive psychology in the instruction of science and technology.